Detection Performance of 99mTc in Albira SI Small-Animal SPECT-CT - Jie TANG; Dong XU; Qianyue HU; Bo ZHANG; Wei LI; Lizhen WANG; Huixin YU; Fukuan ZHAO (Journal of Isotopes)
Small-animal single-photon emission computed tomography-X-ray computed tomography (SPECT-CT) is an advanced imaging tool for preclinical research of single-photon radiopharmaceuticals. Its detection performance is the foundation of image quality and the reliability of experimental data. This study aims to evaluate the performance of Albira SI SPECT-CT in terms of advisable test range，linearity，stability，deviation of measurement results，related to the radioactive isotope 99mTc，and to explore the authenticity and reliability of the scan results.The Albira SI SPECT-CT was subjected to quarterly quality control using the clinically commonly used single-photon radionuclide 99mTc. The linearity，stability，and deviation of the measurement results were tested，and preliminary attempts were made at small-animal bone metabolism scanning. The device demonstrated a strong linear correlation between radioactivity and measurement results，exhibited high stability，and showed minimal variation when compared to commonly used radioactivity measurement devices.The Albira SI small animal SPECT-CT accurately reflects the distribution of the radioactive activity of the single photon isotope 99mTc，showing excellent imaging of mouse bone metabolism，suitable for preclinical radiopharmaceutical research. The method for evaluating SPECT-CT performance established in this study is expected to provide a reference for the operation of similar equipment.